2018
DOI: 10.1038/s41388-018-0461-3
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous cancer-associated fibroblast population potentiates neuroendocrine differentiation and castrate resistance in a CD105-dependent manner

Abstract: Heterogeneous prostatic carcinoma-associated fibroblasts (CAF) contribute to tumor progression and resistance to androgen signaling deprivation therapy (ADT). CAF subjected to extended passaging, compared to low passage CAF, were found to lose tumor expansion potential and heterogeneity. Cell surface endoglin (CD105), known to be expressed on proliferative endothelia and mesenchymal stem cells, was diminished in high passage CAF. RNA-sequencing revealed SFRP1 to be distinctly expressed by tumor-inductive CAF, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(106 citation statements)
references
References 45 publications
(55 reference statements)
2
92
0
Order By: Relevance
“…Androgen deprivation therapy is the gold standard of care for advanced prostate cancer, but the development to castration-resistant prostate cancer is inevitable, ultimately leads to treatment failure and death. Importantly, recent studies have demonstrated that CAFs, as key components of the tumour microenvironment, contributes to PCa progression and resistance to ADT [7][8][9]. Furthermore, mounting studies provided new evidence to the role of CAF-derived exosomes in cancer progression [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Androgen deprivation therapy is the gold standard of care for advanced prostate cancer, but the development to castration-resistant prostate cancer is inevitable, ultimately leads to treatment failure and death. Importantly, recent studies have demonstrated that CAFs, as key components of the tumour microenvironment, contributes to PCa progression and resistance to ADT [7][8][9]. Furthermore, mounting studies provided new evidence to the role of CAF-derived exosomes in cancer progression [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Cultured LNCaP, TRAMPC2, and PC3 (all from ATCC) were grown in Roswell Park Memorial Institute (RPMI) media supplemented with 5% fetal bovine serum and treated with docetaxel (Sano-fiAventis) or SB290157 (1 μM, Calbiochem) for 48 h. Conditioned medium was treated with DNase1 (0.1 mg/mL, Sigma-Aldrich) in 37°C for 1 h followed by heat inactivation. Cultured primary NAF and CAF derived in our laboratory (4) were treated with LNCaP-CM, CpG-ODN (5 μM, InvivoGen), and N-acetylcysteine (10 mM [Sigma-Aldrich]).…”
Section: Methodsmentioning
confidence: 99%
“…Incidentally, higher doses of docetaxel were used for PC3 cells compared to the other two lines due to its inherent resistance. The influence of stromal-epithelial cross talk in the development of docetaxel resistance was tested in coculture studies within a three-dimensional (3D) matrix of collagen I and Matrigel (4,18). The coculture of PC3 and CAF resulted in a doubling of EpCAM + /Ki67 + proliferative epithelia compared to that when PC3 cells were grown alone (Fig.…”
Section: Synergistic Effect Of Docetaxel and C3ar Antagonism Inhibitmentioning
confidence: 99%
See 1 more Smart Citation
“…It was later found that higher preoperative plasma levels of CD105 were associated with poor clinical outcomes of PC such as higher PSA values, higher Gleason scores, and biochemical recurrence after radical prostatectomy (5). The expression of CD105 on cancer associated fibroblasts has been demonstrated to be elevated with and contribute to PC resistance to androgen targeted therapy (6). A study has measured endoglin in urine and serum samples of men at high risk of PC (7).…”
mentioning
confidence: 99%